2000
DOI: 10.1080/0028825x.2000.9512695
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and vegetative morphology of the carnivorous plantUtricularia dichotorna(Lentibulariaceae) in New Zealand

Abstract: Among the populations studied, the corolla, peduncle, foliage leaf, and bladders occasionally exhibited a reddish or purple pigmentation, apparently developed in a response to different environmental factors.Keywords Utricularia dichotoma; Lentibulariaceae; carnivorous plant; vegetative morphology; anthocyanins; stolon; traps; vegetation ecology; wetlands Abstract The occurrence of the carnivorous plant Utricularia dichotoma (including U. monanthos and U. novae-zelandiae) within different habitats throughout N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Brugger and Rutishauser 1989;Rutishauser 2016). This variability was confirmed by Reut and Fineran (2000) on plants from U. dichotoma and thought to be correlated with the micro-habitat.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Brugger and Rutishauser 1989;Rutishauser 2016). This variability was confirmed by Reut and Fineran (2000) on plants from U. dichotoma and thought to be correlated with the micro-habitat.…”
Section: Introductionmentioning
confidence: 76%
“…Memb ers of sections Polypompholyx and Tridentaria and some species of section Pleiochasia grow as rosette plants with foliage leaves, anchor stolons (rhizoids), bladders and inflorescences deriving from a short stem (Taylor 1989;Jobson et al 2018). However, species of section Lasiocaules and most species of section Pleiochasia, including U. dichotoma, additionally produce runner stolons which may carry leaves, several types of branched and unbranched stolons, bladders and occasionally inflorescences (Merl 1915;Lloyd 1942;Taylor 1989;Reut and Fineran 2000;Jobson et al 2018). In determined position on a stolon of terrestrial and aquatic utricularias, types and numbers of organs have been found to vary to a certain degree (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have documented that vegetative morphology varies with environmental conditions , Reut and Fineran 2000 Quantitative data taken included the number of flowers per inflorescence ( U cornuta and Ujuncea) and the number of segments and the diameter ofthe whorl ofinflated vegetative structures surrounding the inflorescence penduncle ( U radiata and U inflata).…”
Section: Introductionmentioning
confidence: 99%